Analysis of Risk and Return on Investments in Cryptocurrency Instruments in Indonesia from 2022 to 2024 - Rizki Hidayat; Renny Maisyarah (Transpublika Publisher, 2025)
Cryptocurrency has a much higher level of risk and volatility compared to traditional investment instruments such as stocks, thus requiring a deeper understanding of the characteristic differences between the two. This research analyzes the risk profile and return on investment of cryptocurrency compared to stock indices in Indonesia during the 2022–2024 period. This research seeks to examine the characteristic differences between cryptocurrency and traditional stock investments. Using purposive sampling techniques, this research involves five types of cryptocurrency (Bitcoin, Ethereum, Tether, Binance, Ripple) and five stock indices (IHSG, MBX, LQ45, Kompas 100, Bisnis-27) with monthly data totaling 350 observations. The methodology used includes the Shapiro-Wilk normality test for data distribution, followed by the non-parametric Mann-Whitney U test for return and risk variables that are not normally distributed, and the Independent Sample t-test for the Value at Risk (VaR) variable that is normally distributed. The findings shed light that although there is no significant difference in the rate of return between cryptocurrency and stock indices (p = 0.494), cryptocurrency has a much higher level of risk based on standard deviation (p = 0.000) and Historical VaR 95% (p = 0.028). The average VaR of cryptocurrency reaches 23.17%, while stock indices only 6.10%, indicating a potential maximum loss nearly four times greater under worst market conditions. These findings confirm that cryptocurrency is a high-risk asset that demands more careful risk management strategies, and provides important implications for investors and policymakers in designing regulations and investment portfolios that are adaptive to digital market dynamics.